Molecular and Cellular Mechanisms of Apoptosis during Dissociated Spermatogenesis - Liu, Tengfei; Wang, Lingling; Chen, Hong; Huang, Yufei; Yang, Ping; Ahmed, Nisar; Wang, Taozhi; Liu, Yi; Chen, Qiusheng (Frontiers in Physiology, 2017)
Apoptosis is a tightly controlled process by which tissues eliminate unwanted cells. Spontaneous germ cell apoptosis in testis has been broadly investigated in mammals that have an associated spermatogenesis pattern. However, the mechanism of germ cell apoptosis in seasonally breeding reptiles following a dissociated spermatogenesis has remained enigmatic. In the present study, morphological evidence has clearly confirmed the dissociated spermatogenesis pattern in Pelodiscus sinensis. TUNEL and TEM analyses presented dynamic changes and ultrastructural characteristics of apoptotic germ cells during seasonal spermatogenesis, implying that apoptosis might be one of the key mechanisms to clear degraded germ cells. Furthermore, using RNA-Seq and digital gene expression (DGE) profiling, a large number of apoptosis-related differentially expressed genes (DEGs) at different phases of spermatogenesis were identified and characterized in the testis. DGE and RT-qPCR analysis revealed that the critical anti-apoptosis genes, such as Bcl-2, BAG1 and BAG5, showed up-regulated patterns during intermediate and late spermatogenesis. Moreover, the increases in mitochondrial transmembrane potential in July and October were detected by JC-1 staining. Notably, the low protein levels of pro-apoptotic cleaved caspase-3 and CytC in cytoplasm were detected by immunohistochemistry and western blot analyses, indicating that the CytC-Caspase model might be responsible for the effects of germ cell apoptosis on seasonal spermatogenesis. These results facilitate understanding the regulatory mechanisms of apoptosis during spermatogenesis and uncovering the biological process of the dissociated spermatogenesis system in reptiles.